Subsurface Investigation of Oligocene Geologic Formations Age, East Baghdad Oil Field - Khorshid, Salman; Kadhm, Ayat (Iraqi Journal of Science, 2025)
An investigate of the subsurface of East Baghdad Oil field South-1 and South-2, by using the interactive workstation Geoframe. The study is interested with Oligocene Formations which is an extension of Kirkuk group. Synthetic seismogram is generated from data of EB-15 well. Base of Lowe-Fars reflector is picked and identified because it is close to Jeribe Formation that was deposited in the same depositional environment of Kirkuk group. The seismic sections and time slice maps confirmed that the Oligocene age was not affected by faults and the signs or indicators of faults started from Hartha Formation and continue to the deeper formations with increasing intensity, where the variance attribute section was applied on time slice and shows that the area was affected by listric growth normal fault parallel to the structure of the field trends (NW-SE) and affected by number of transverse faults trend (E-W) and (NE-SW). Time map, velocity map and depth map of base Lower-Fars reflector depending on data from (EB-2, EB-4, EB-5, EB-6, EB-15, EB-24), the maps was showed the structural picture of East Baghdad that formed structural nose opened toward NW and trending (NW-SE) that confirmed by 3D volume which prepared for the studied area. By studying the seismic sections and applying seismic attributes(instantaneous phase, reflection magnitude, and variance attributes) discovered the presence of Direct Hydrocarbon Indicator at shallow depth in Oligocene age represented by flat spot at Bajwan/Baba Formation and dim spot below Dhiban/ Euphrates Formations in locations inlines 49235, 49225, 49190, and 49095, cross line 11700. Further confirmation on the presence of Direct Hydrocarbon Indicator is outlined from the application of flattening technique on seismic and attributes sections. Finally the surface area of the spreading of spot has been calculated in MESA expert 11.02 program that reaches approximately 13.47 km2.